Clima organizacional en relación al desempeño laboral de los trabajadores de Caja Municipal de Ahorro y Crédito Paita Chepén 2014. - Correa Perez, Giovanna Lisett (2014)
The purpose of this research is to determine how these factors affect Organizational Climate to improve Workers Work Performance of the CMAC Paita - Chepén. The research is descriptive and prospective population consisted of 15 workers of the CMAC Paita- Chepén city, working in this organization in 2014. Propositional descriptive design was used to test the hypothesis. Also a survey questionnaire was employed workers to the company, the sales area to assess their organizational development. After obtaining the information of 15 workers, it was determined that they need strategies, incentives, support from their bosses so they can perform in a better way, ie more eager to meet their goals. In this thesis, each question of the questionnaire was analyzed and plotted graphically, these results were the basis for the formulation of strategies for better job performance, I also wonder about how they felt in their work environment.